A simple and practical workflow for genotyping of CRISPR–Cas9‐based knockout phenotypes using multiplexed amplicon sequencing. (25th May 2020) - Iida, Midori; Suzuki, Miyuki; Sakane, Yuto; Nishide, Hiroyo; Uchiyama, Ikuo; Yamamoto, Takashi; Suzuki, Ken‐ichi T.; Fujii, Satoshi
Abstract: Founder animals carrying high proportions of somatic mutation induced by CRISPR–Cas9 enable a rapid and scalable strategy for the functional screening of numerous target genes in vivo. In this functional screening, genotyping using pooled amplicons with next‐generation sequencing is the most suitable approach for large‐scale management of multiple samples and accurate evaluation of the efficiency of Cas9‐induced somatic mutations at target sites. Here, we present a simple workflow for genotyping of multiple CRISPR–Cas9‐based knockout founders by pooled amplicon sequencing. Using custom barcoded primers, pooled amplicons from multiple individuals can be run in a single‐indexed library on the Illumina MiSeq platform. Additionally, a user‐friendly web tool, CLiCKAR, is available to simultaneously perform demultiplexing of pooled sequence data and evaluation of somatic mutation in each phenotype. CLiCKAR provides users with practical reports regarding the positions of insertions/deletions, as well as the frameshift ratio and tables containing mutation sequences, and read counts of each phenotype, with just a few clicks by the implementation of demultiplexing for pooled sample data and calculation of the frameshift ratio. This genotyping workflow can be harnessed to evaluate genotype–phenotype correlations in CRISPR–Cas9‐based loss‐of‐function screening of numerous target genes in various organisms. Abstract : A simple and practical workflow for genotyping of CRISPR‐Cas9‐based knockout phenotypes using multiplexed amplicon sequencing.